After genomic testing results: Parents' long‐term views. Issue 1 (24th June 2021) - Liang, Nicole Si Yan; Adam, Shelin; Elliott, Alison M.; Siemens, Angela; du Souich, Christèle; ,; ,; Friedman, Jan M.; Birch, Patricia
Abstract: Many parents are motivated to pursue genome‐wide (exome or genome) sequencing to find a diagnosis for their child with a suspected but undiagnosed genetic condition. However, the impact of the genomic test extends beyond the provision of results and the so‐called 'diagnostic odyssey'. Our goal was to quantify post‐test decisional regret and characterize long‐term, post‐test experiences and unmet needs of the parents of children with suspected genetic diseases after they had received the results of genome‐wide sequencing. Study participants were parents of children who underwent trio genome‐wide sequencing as part of the CAUSES research study at Children's & Women's Health Centre of British Columbia. About half of the participants received a definite or likely genetic diagnosis after clinical interpretation of the genome‐wide sequencing results. Parents who participated in the current study ( n  = 121) completed the Decisional Regret Scale four weeks after receiving results. A subset of these parents ( n  = 32) had semi‐structured interviews a median of 7 months (range 3–20 months) after results disclosure and post‐test genetic counseling. Most parents expressed either no regret or mild regret about having undergone genome‐wide sequencing on both the Decisional Regret Scale and in the interviews. Parents whose children did not receive a genetic diagnosis were slightly more likely to have decisional regret on this quantitative scale. Analysis of transcribed interviews revealed the following major themes: (a) a lack of decisional conflict around having the testing; (b) a lack of decisional regret post‐testing; (c) expressions of both relief and continued uncertainty around the meaning of a genetic diagnosis; (d) expression of initial disappointment and evolving interpretation surrounding a result yielding no genetic diagnosis; and (e) needing time to absorb the test results. Our results suggest that parents need time to absorb the testing results and that long‐term post‐test counseling, including acknowledging feelings of relief, loss, and disappointment, may help parents adapt to the genomic test results and assist families to anticipate and plan for the next steps in their child's medical trajectory, whether or not a diagnosis is found.